205 Changes in Sleep Due to COVID Pandemic Associated with Changes to Dietary Patterns. (3rd May 2021) - Ghani, Sadia; Kennedy, Kathryn; Seixas, Azizi; Jean-Louis, Giardin; Killgore, William; Knowlden, Adam; Wills, Chloe; Grandner, Michael
Abstract: Introduction: The COVID-19 pandemic has affected sleep and diet for many people. The present study sought to examine potential associations between changes to sleep and eating habits during the COVID-19 pandemic. Methods: A sample of N=419 US adults completed online surveys about sleep and COVID-19 experiences. Questions for diet asked, "since quarantine: I'm eating healthier, eating more processed foods, home-cooked meals and more regularly, " "I'm enjoying food in quarantine and I'm struggling with overeating in quarantine." Sleep questions asked "since quarantine: I have managed to keep a regular sleep-wake schedule, my sleep has improved, I'm struggling to fall asleep, I'm waking up more during the night, I'm more sleepy during the day and I'm taking more naps during the day." Answers were reported on a 4-point scale ranging from "strongly disagree to strongly agree." Ordinal logistic regressions were used, adjusted for age and sex and examined each dietary variable as ordinal outcome and each sleep variable as predictor. Results: Those who report that they kept a more regular schedule were more likely to report eating healthier (oOR=3.13, p=0.007), eating more home-cooked meals (oOR=3.19, p=0.005), and less likely to be eating more processed foods (oOR=0.39, p=0.02), struggle with overeating (oOR=0.39, p=0.02) or undereating (oOR=0.30, p=0.004) or snacking (oOR=0.25, p=0.001). Those reporting more difficulty falling asleep were less likely to be eating healthier (oOR=0.25, p=0.002) and more likely to be eating more processed foods (oOR=3.07, p=0.009) and snacking (oOr=2.36, P=0.04). Those reporting more difficulty with awakenings were less likely to report eating healthier (oOR=0.34, p=0.03) and more likely to report eating more processed foods (oOR=4.52, p=0.001). Those with more sleepiness were less likely to report eating healthier (oOR=0.29, p=0.01) and more homecooked meals (oOR=0.40, p=0.046) and more likely to report eating more processed foods (oOR=6.42, p<0.0005), overeating (oOR=3.63, p=0.01) and snacking (oOR=5.81, p=0.001). Conclusion: Research studying psychological, behavioral and environmental factors that are contributing to changes in sleep and dietary patterns is especially important during a pandemic that has forced people into changes that they may not have been prepared for and which may result in long-term health outcomes. Support (if any): T32HL007249, R01MD011600, R01DA051321